METTL3 affects the biological function of lung adenocarcinoma through the FGF2/PI3K/AKT /mTOR pathway - Chen, Shaoting; Shen, Xiuqing; Cao, Pengju; Chen, Qianshun; Zhong, Rongxin; Cao, Yingping (Frontiers in Oncology, 2024)
IntroductionThis study aims to investigate the role of the m6A regulatory factor METTL3 in LUAD.MethodsBy examining the expression of METTL3 in LUAD and conducting cellular functional experiments, the biological functions of METTL3 were discussed. mRNA-seq and MeRIP-qPCR were used to identify downstream target genes and pathways.ResultsThe expression level of METTL3 in LUAD is lower than that in the control group. The downregulation of METTL3 promoted the proliferation, migration, and invasion of LUAD cells, while overexpression of METTL3 results in the opposite effects. Furthermore, we found that FGF2 was negatively regulated by METTL3. Inhibiting FGF2 reversed the tumor-promoting effects caused by METTL3 downregulation in LUAD cells. Silencing METTL3 enhanced the stability of FGF2 mRNA. Silencing FGF2 resulted in reduced activity of the PI3K/AKT/mTOR signaling pathway in METTL3 knockdown LUAD cells.DiscussionIn summary, our findings unveil an intricate signaling network involving METTL3/FGF2/PI3K/AKT/mTOR in LUAD and provide valuable insights into the molecular mechanisms underlying tumor progression, thus holding significant implications for targeted therapy and advancing LUAD research.